2021
DOI: 10.1007/s40495-021-00253-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of New and Emerging Drugs for COVID-19: Favipiravir and Dexamethasone

Abstract: Purpose of Review The widespread respiratory disease of virus known as severe acute respiratory syndrome–coronavirus 2019 (SAR-CoV-2) had infected more than 200 countries and caused pandemic and havoc in the world. Recent Findings The genome of the virus was sequenced rapidly to study its mechanism, epidemiology, drugs, and vaccines. Many drugs and vaccines are being studied by researchers to treat and prevent the SARS-CoV-2. Favipiravir and dexamethasone are repurposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(8 reference statements)
0
13
0
1
Order By: Relevance
“…This drug offers the most costeffective treatment for COVID-19 which can reduce mortality by 20% in patients on oxygen therapy and by 30% in patients on automatic ventilation (14). It also has an anti-viral effect by binding to the hormone cortisol, stimulating the production of anti-inflammatory cytokines and inhibiting the secretion of proinflammatory cytokines that cause COVID-19 pneumonia (15).…”
Section: Introductionmentioning
confidence: 99%
“…This drug offers the most costeffective treatment for COVID-19 which can reduce mortality by 20% in patients on oxygen therapy and by 30% in patients on automatic ventilation (14). It also has an anti-viral effect by binding to the hormone cortisol, stimulating the production of anti-inflammatory cytokines and inhibiting the secretion of proinflammatory cytokines that cause COVID-19 pneumonia (15).…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir has been studied in patients with 2019-nCoV in randomized trials in mice, the results suggest further in vivo studies are recommended to evaluate this antiviral nucleoside efficiency [66]. Clinical trials in China and Japan showed good potential for favipiravir use against COVID-19 [134].…”
Section: Favipiravirmentioning
confidence: 99%
“…Favipiravir is the antiviral drug of choice for the treatment of COVID-19 in some countries ( Figure 1 ), including Russia, India, Japan, Saudi Arabia, and Turkey [1] . Treatment protocol varies from country to country.…”
Section: Introductionmentioning
confidence: 99%